Development of Student Worksheets (LKPD) Using Problem Based Learning Models on Flat Shape Materials - Syafira Fuad, Annisa (Jurnal Riset Ilmu Pendidikan, 2022)
he formulation of the problem in this research are: How is LKPD Development Using Problem Based Learning Model on Flat Shape Material? Is LKPD using problem-based learning model feasible as a learning medium for students? How are students' responses to LKPD using Problem Based Learning model? This study aims to produce LKPD products using a problem-based learning model on valid and feasible flat-shaped materials. This research is a type of development research and uses 4-D (four-D) research procedures which are modified into 3-D (three-D), namely the definition stage, the design stage, and the development stage. The results of this study: 1) researchers have produced LKPD using a problem based learning model on the material of flat shapes, the subject of circumference and area of ??a triangle; 2) the results of the assessment of student worksheets from material experts are 81.5% with a fairly valid level of validity and the assessment of LKPD from media experts is 83.5% with a fairly valid level of validity; 3) obtaining the results of the assessment through a student response questionnaire with an average percentage of 85.96% with a very positive category. From the results of the assessment of material experts, media experts and student responses, the LKPD developed is valid and feasible to be used as a learning medium by students.